2014
DOI: 10.1111/cyt.12166
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics for the diagnosis of thyroid lesions: preliminary report

Abstract: Our results confirmed the possible role of MALDI-IMS in the search for diagnostic targets of PTC and follicular lesions, which could be applied in larger trials aimed at the identification of proteins, convertible to cost-effective diagnostic tools such as immunohistochemistry. These tests could be used to analyse in vivo cytological smears, improving the preoperative diagnosis of indeterminate thyroid nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 13 publications
2
26
0
Order By: Relevance
“…Mainini et al [69] performed a preliminary test on various types of lesions including cvPTC, fvPTC, hyperplastic nodules, and uncertain malignant potential tumors, attempting a classification of these conditions based on hierarchical cluster analysis and principal component analysis of protein expression spectra. Analog results were obtained by Pagni et al [70] in their feasibility study, applying MALDI imaging on a set of various lesions as hyperplastic nodules, Hurtle cell-type FTA, medullary thyroid carcinoma, and cvPTC, showing similar spectra of protein expression between entities with similar biological behavior.…”
Section: Proteomics On Thyroid Cytological Samplessupporting
confidence: 77%
See 1 more Smart Citation
“…Mainini et al [69] performed a preliminary test on various types of lesions including cvPTC, fvPTC, hyperplastic nodules, and uncertain malignant potential tumors, attempting a classification of these conditions based on hierarchical cluster analysis and principal component analysis of protein expression spectra. Analog results were obtained by Pagni et al [70] in their feasibility study, applying MALDI imaging on a set of various lesions as hyperplastic nodules, Hurtle cell-type FTA, medullary thyroid carcinoma, and cvPTC, showing similar spectra of protein expression between entities with similar biological behavior.…”
Section: Proteomics On Thyroid Cytological Samplessupporting
confidence: 77%
“…The validation via ELISA and WB confirmed the role of these proteins in discriminating PTC from controls and ANXA1 showed a sensitivity of 87% and a specificity of 94% in distinguishing cancer from normal cases. Recent studies showed how MALDI-MSI can be used to investigate ex vivo FNA specimens [69,70]. Mainini et al [69] performed a preliminary test on various types of lesions including cvPTC, fvPTC, hyperplastic nodules, and uncertain malignant potential tumors, attempting a classification of these conditions based on hierarchical cluster analysis and principal component analysis of protein expression spectra.…”
Section: Proteomics On Thyroid Cytological Samplesmentioning
confidence: 99%
“…Techniques such as matrix-assisted laser desorption/ionization (MALDI)-TOF-MS and MALDI-imaging mass spectrometry (MALDI-IMS) have been applied in several studies [90,91,92,93,94,95] to cytological thyroid specimens. Most of these studies used ex vivo FNA [90,91,93,94,95] and one study [94] used pre-surgical FNAC obtaining an overall sensitivity of 87% and specificity of 94% in discriminating benign from suspicious samples, with a good reproducibility among studies. Proteomics could serve to improve the preoperative diagnosis of indeterminate lesions, but some aspects such as the limitation in the availability of these technologies and the lack of uniformity among techniques, need to be addressed before its introduction in clinical practice.…”
Section: Proteomics: An Interesting Alternative Approach To Stratimentioning
confidence: 99%
“…Among the localized proteins, ribosomal protein P2 was found specific for cancerous tissues . Other preliminary studies by MSI were performed for thyroid fine needle aspiration smears .…”
Section: Applications Of Msi In Cancer Diagnosis Staging and Prognosismentioning
confidence: 99%